Rotational Rigid Body Symmetry Modes: A Tool for the Investigation of Phase Transitions. Issue 15 (5th November 2014) - Etter, Martin; Müller, Melanie; Dinnebier, Robert E.
Abstract Phase transitions recorded using in‐situ powder diffraction are typically analysed by Rietveld refinements applying relative atomic coordinates in a least‐squares iteration process. Although this choice of relative atomic coordinates gives an intuitive coordinate system, it can be improved by changing to another basis of the atomic configuration space, as the motion of whole atomic groups or polyhedra can be normally described with a smaller set of parameters. Using rotational rigid body symmetry modes as another basis, it is possible to directly describe and refine the rotation of groups of atoms (denoted as constrainable atomic groups). In addition, a reduction of the total number of relevant parameters can occur. In order to explore the capabilities of this new approach, phase transitions in different compounds, namely sodium niobate (NaNbO3), ferrocene (Fe(C5H5)2), and schafarzikite (FeSb2O4) are reinvestigated.